Learning curve of ultrasound-guided caudal epidural block: a CUSUM pivotal analysis - Ma, Dongmei; Chen, Ping; Xu, Jianhong (Frontiers in Medicine, 2025)
Background and objectivesThis study aims to dynamically evaluate the learning curve of anesthesiology residents’ mastery of ultrasound-guided caudal epidural block (US-CEB) through cumulative summation (CUSUM) analysis, providing a quantitative basis for optimizing the training program.MethodsAfter ethical approval and registration, 10 novice anesthesiology residents underwent standardized training in US-CEB. Over 4 months, each of 10 residents performed 30 procedures, totalling 300 cases on 300 patients undergoing perineal and sacrococcygeal surgeries. The CUSUM analysis was applied to measure performance in terms of success rates, procedural times and self-confidence score.ResultsThe learning curve had two phases: rapid skill acquisition followed by a plateau indicating proficiency. The median time for participants to identify landmarks was 49.5 s, and the US-CEB procedure took 146.6 s. Landmark identification skills plateaued after about 9 procedures, US-CEB skills after 11, and self-confidence after 13. Polynomial modeling showed a strong non-linear relationship between procedures and performance, with high R2 values.ConclusionThe study shows that US-CEB can be learned quickly with targeted training. A structured initial training and deliberate practice help residents master ultrasound-guided sacral canal block procedures. As operators improve their skills, their confidence increases, fostering continuous development and mastery.